Rat NaV1.7 loss-of-function genetic model: Deficient nociceptive and neuropathic pain behavior with retained olfactory function and intra-epidermal nerve fibers. (October 2019) - Grubinska, B; Chen, L; Alsaloum, M; Rampal, N; Matson, DJ; Yang, C; Taborn, K; Zhang, M; Youngblood, B; Liu, D; Galbreath, E; Allred, S; et al.
Recapitulating human disease pathophysiology using genetic animal models is a powerful approach to enable mechanistic understanding of genotype–phenotype relationships for drug development. NaV 1.7 is a sodium channel expressed in the peripheral nervous system with strong human genetic validation as a pain target. Efforts to identify novel analgesics that are nonaddictive resulted in industry exploration of a class of sulfonamide compounds that bind to the fourth voltage-sensor domain of NaV 1.7. Due to sequence differences in this region, sulfonamide blockers generally are potent on human but not rat NaV 1.7 channels. To test sulfonamide-based chemical matter in rat models of pain, we generated a humanized NaV 1.7 rat expressing a chimeric NaV 1.7 protein containing the sulfonamide-binding site of the human gene sequence as a replacement for the equivalent rat sequence. Unexpectedly, upon transcription, the human insert was spliced out, resulting in a premature stop codon. Using a validated antibody, NaV 1.7 protein was confirmed to be lost in the brainstem, dorsal root ganglia, sciatic nerve, and gastrointestinal tissue but not in nasal turbinates or olfactory bulb in rats homozygous for the knock-in allele (HOM-KI). HOM-KI rats exhibited normal intraepidermal nerve fiber density with reduced tetrodotoxin-sensitive current density and action potential firing in small diameter dorsal root ganglia neurons. HOM-KI rats did not exhibit nociceptive pain responses in hot plate or capsaicin-induced flinching assays and did not exhibit neuropathic pain responses following spinal nerve ligation. Consistent with expression of chimeric NaV 1.7 in olfactory tissue, HOM-KI rats retained olfactory function. This new genetic model highlights the necessity of NaV 1.7 for pain behavior in rats and indicates that sufficient inhibition of NaV 1.7 in humans may reduce pain in neuropathic conditions. Due to preserved olfactory function, this rat model represents an alternative to global NaV 1.7 knockout mice that require time-intensive hand feeding during early postnatal development.